2023
DOI: 10.1097/rli.0000000000000957
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons in Vascular Imaging With Photon-Counting Detector CT

Abstract: Noninvasive vascular imaging with computed tomography (CT) has become the clinical mainstay for many indications and body regions. The recent introduction of photon-counting detector (PCD)-CT into clinical routine has further broadened the spectrum of vascular applications. Technical improvements of PCD-CT, such as the decreased noise levels, improved contrast-to-noise ratio, and full spectral multienergy data information from every acquisition, have the potential to further impact on clinical decision making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The PCCT technology promises scalable higher spatial resolution and less blooming, with comparable or even lower patient dose than conventional EICT. 1,95,96 First phantom experiments demonstrated gradual improvements. In-stent lumen visualization in 18 different stents in vitro was improved with an experimental PCCT system (SOMATOM CounT) as compared with EICT, although image reconstruction was performed with a B46 kernel, which does not fully exploit the inherent spatial resolution.…”
Section: Cardiac Imaging and Ai-based Motion Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCCT technology promises scalable higher spatial resolution and less blooming, with comparable or even lower patient dose than conventional EICT. 1,95,96 First phantom experiments demonstrated gradual improvements. In-stent lumen visualization in 18 different stents in vitro was improved with an experimental PCCT system (SOMATOM CounT) as compared with EICT, although image reconstruction was performed with a B46 kernel, which does not fully exploit the inherent spatial resolution.…”
Section: Cardiac Imaging and Ai-based Motion Compensationmentioning
confidence: 99%
“…They reported improved lumen visibility in the presence of calcified plaque and stents (80% of stents with a diameter of 2.5 mm or more were considered assessable), but average patient dose increased from 2.9 mSv (Aquilion One) to 7.4 mSv (UHR). The PCCT technology promises scalable higher spatial resolution and less blooming, with comparable or even lower patient dose than conventional EICT 1,95,96 . First phantom experiments demonstrated gradual improvements.…”
Section: Cardiac Imaging and Ai-based Motion Compensationmentioning
confidence: 99%
“…To date, already several studies have shown advantages of PCD-CT over conventional CT, [6][7][8] including applications for abdominal, vascular, cardiac, or chest imaging and various other fields of radiology may benefit from the new detector technique. [9][10][11][12] In this review, we summarize the current status of PCD-CT with regards to applications focusing on the central nervous system and the head and neck region. We review the existing literature and highlight promising future applications.…”
mentioning
confidence: 99%
“…The benefit of these new, technically guided opportunities is subject of intensive ongoing research. To date, already several studies have shown advantages of PCD-CT over conventional CT, 6–8 including applications for abdominal, vascular, cardiac, or chest imaging and various other fields of radiology may benefit from the new detector technique 9–12 . In this review, we summarize the current status of PCD-CT with regards to applications focusing on the central nervous system and the head and neck region.…”
mentioning
confidence: 99%
“…12 Dr Fides Schwartz from the Duke University Medical Center explores the possibilities and potential of photon-counting detector CT in abdominal imaging. 13 Dr Joachim Wildberger from the Maastricht University discusses the current experience and research on the new horizons in vascular imaging with photon-counting detector CT, 14 whereas Dr Zsarnoczay and colleagues from the Medical University of South Carolina, Charleston explore the new options for characterizing the heart and myocardium with photon-counting detector CT. 15 Finally, Dr Gregor Jost and colleagues from the Bayer AG, Berlin detail the current research and future developments on new contrast agents for k-edge imaging tailed to photon-counting detector CT. 16 We are grateful to each author for their contributions, for their dedication, their scientific approach in exploiting the potential of this new technique, and for their ability to explain this new technology to the readers in an understandable fashion and with impressive illustrations. We believe that the review articles of this special issue will serve as long-term references for current and future physicians, physicists, and scientists alike.…”
mentioning
confidence: 99%